School as a space of activities and possibilities. Ethnographic case study of the school of The Civic Educational Association in Warsaw - Marta Krasuska-Betiuk; Edyta Żebrowska (Studia z Teorii Wychowania)
The issues of the text have been addressed in the area of school pedagogy; its purpose is to describe the capital's institution through the prism of selected values. The subject of the analyses, carried out in the interpretative paradigm, focuses on the category of the axiological space of school, reconstructed from the program concept and pedagogy present in the journalistic educational discourse of the head teacher of this community school. An important dimension of the culture of the described school is relational trust, which is why the article sets out the conditions conducive to its existence.